Attending Heart School and long-term outcome after myocardial infarction: A decennial SWEDEHEART registry study. (29th August 2020) - Wallert, John; Olsson, Erik MG; Pingel, Ronnie; Norlund, Fredrika; Leosdottir, Margret; Burell, Gunilla; Held, Claes
Abstract: Background: The Heart School is a standard component of cardiac rehabilitation after myocardial infarction in Sweden. The group-based educational intervention aims to improve modifiable risks, in turn reducing subsequent morbidity and mortality. However, an evaluation with respect to mortality is lacking. Aims: Using linked population registries, we estimated the association of attending Heart School with both all-cause and cardiovascular mortality, two and five years after admission for first-time myocardial infarction. Methods: Patients with first-time myocardial infarction (<75 years) were identified as consecutively registered in the nationwide heart registry, SWEDEHEART (2006–2015), with >99% complete follow-up in the Causes of Death registry for outcome events. Of 192, 059 myocardial infarction admissions, 47, 907 unique patients with first-time myocardial infarction surviving to the first cardiac rehabilitation visit constituted the study population. The exposure was attending Heart School at the first cardiac rehabilitation visit 6–10 weeks post-myocardial infarction. Data on socioeconomic status was acquired from Statistics Sweden. After multiple imputation, propensity score matching was performed. The association of exposure with mortality was estimated with Cox regression and survival curves. Results: After matching, attending Heart School was associated (hazard ratio (95% confidence interval)) with a markedly lower risk of both all-cause (two-year hazard ratio = 0.53 (0.44–0.64); five-year hazard ratio = 0.62 (0.55–0.69)) and cardiovascular (0.50 (0.38–0.65); 0.57 (0.47–0.69)) mortality. The results were robust in several sensitivity analyses. Conclusions: Attending Heart School during cardiac rehabilitation is associated with almost halved all-cause and cardiovascular mortality after first-time myocardial infarction. The result warrants further investigation through adequately powered randomised trials.